Biomechanical comparison of anterior axis-atlanto-occipital transarticular fixation and anterior atlantoaxial transarticular fixation after odontoidectomy: A finite element analysis - Lu, Yuzhao; Hang, Gai; Feng, Yu; Chen, Bo; Ma, Shenghui; Wang, Yang; Xie, Tianhao (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Anterior axis-atlanto-occipital transarticular fixation (AAOF) and anterior atlanto-axial transarticular fixation (AAF) are two common anterior screw fixation techniques after odontoidectomy, but the biomechanical discrepancies between them remain unknown. Objectives: To investigate the biomechanical properties of craniovertebral junction (CVJ) after odontoidectomy, with AAOF or AAF. Methods: A validated finite element model of the intact occipital-cervical spine (from occiput to T1) was modified to investigate biomechanical changes, resulting from odontoidectomy, odontoidectomy with AAOF, and odontoidectomy with AAF. Results: After odontoidectomy, the range of motion (ROM) at C1-C2 increased in all loading directions, and the ROM at the Occiput-C1 elevated by 66.2%, 57.5%, and 41.7% in extension, lateral bending, and torsion, respectively. For fixation models, the ROM at the C1-C2 junction both observably reduced after odontoidectomy with AAOF and odontoidectomy with AAF. In addition, at the Occiput-C1, the ROM of odontoidectomy with AAOF model was notably lower than the normal model in extension (94.9%), flexion (97.6%), lateral bending (91.8%), and torsion (96.4%). But compared with the normal model, in the odontoidectomy with AAF model, the ROM of the Occiput-C1 increased by 52.2%, -0.1%, 92.1%, and 34.2% in extension, lateral bending, and torsion, respectively. Moreover, there were no distinctive differences in the stress at the screw-bone interface or the C2-C3 intervertebral disc between the two fixation systems. Conclusions: AAOF can maintain CVJ stability at the Occiput-C1 after odontoidectomy, but AAF cannot. Thus, for patients with pre-existing atlanto-occipital joint instability, AAOF is more suitable than AAF in the choice of anterior fixation techniques.